EFFECTS OF SODIUM NITROPRUSSIDE ON SALT STRESS TOLERANCE OF TOCOPHEROL-DEFICIENT ARABIDOPSIS THALIANA PLANTS - Nadiia Mosiichuk (Vasyl Stefanyk Precarpathian National University, 2015)
In the present study, effects of exogenous sodium nitroprusside (SNP), a nitric oxide (•NO) donor, on lipid peroxidation and antioxidant enzyme activities in wild type and tocopherol-deficient lines vte1 and vte4 of Arabidopsis thaliana subjected to 200 mM NaCl were studied. In wild type plants, pretreatment with SNP did not change level of thiobarbituric acid reactive substances (TBARS), but decreased the activities of dehydroascorbate reductase and guaiacol peroxidase under salt stress. In mutant line vte1, which lacks all forms of tocopherols, pretreatment with SNP reduced TBARS level and increases the activities of glutathione reductase and guaiacol peroxidase under salt stress. Ascorbate peroxidase activity decreased under salt stress conditions in both mutant lines, pretreated with SNP. It can be concluded, that pretreatment with SNP could attenuate salt-induced injuries in A. thaliana plants via up-regulation of activity of antioxidant enzymes and attenuate lipid peroxidation.